Disparities in the Age-Related Rates of Colorectal Cancer in the United States. Issue 6 (June 2017) - Gabriel, Emmanuel; Ostapoff, Katherine; Attwood, Kristopher; Al-Sukhni, Eisar; Boland, Patrick; Nurkin, Steven
The incidence of colorectal cancer (CRC) among Americans under the age of 50 years is increasing. The purpose of this study was to identify racial and socioeconomic disparities associated with this trend. The National Cancer Data Base was used to identify patients with CRC from 1998 to 2011. Patients were stratified by age (<50 versus >60 years), with ages 50 to 60 years omitted from the analysis to minimize overlapping trends between the two age groups. Relative frequencies (RFs) by year were plotted against demographic variables. Changes in RF over time and intervals from diagnosis to treatment (including surgery and chemotherapy) were compared. A total of 1, 213, 192 patients were studied; 885, 510 patients with colon cancer and 327, 682 with rectal or rectosigmoid cancer. Patients <50 years had higher RF for stage III/IV CRC compared with >60 years, with the highest rate of increase in stage III colon cancer (0.198% per year). Patients <50 years had higher RF for CRC if they were African-American or Hispanic. Hispanic patients <50 years had the highest rates of increase for both colon (RF = 0.300% per year) and rectal cancer (RF = 0.248% per year). Compared with race, other variables including education and income were not found to have as strong an association on age-related rates of CRC. No clinically significant differences were observed for time from diagnosis to treatment in either age group. Important racial disparities are associated with differences in age-related CRC rates, warranting further investigation to develop improved strategies for the earlier detection of CRC in these populations.